Verification of performances enhancement by array configuration technique in patch antenna design for energy harvesting applications - Hamid S.H.A.; Hock G.C.; Ferdous N. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper presented the analysis of element in designing a micro strip patch antenna. A single element of the circular patch antenna and 1x2 array elements of circular patch antennas were simulated, fabricated, measured, analyzed, and discussed in this work. Array configuration study is the essence of this research. In order to improve the performances of an antenna, the implementation of array configuration is one of the techniques in designing the patch antenna. Based on the results, it has been verified that an array configuration technique works in enhances and improves the patch antenna performances. This paper also discussed the fabrication process involves and comparison of performances between simulation and measurement. BEIESP.